Cost‐effectiveness of a motivational interviewing obesity intervention versus usual care in pediatric primary care offices. Issue 11 (2nd November 2022) - Woolford, Susan J.; Resnicow, Kenneth; Davis, Matthew M.; Nichols, Lauren P.; Wasserman, Richard C.; Harris, Donna; Gebremariam, Achamyeleh; Shone, Laura; Fiks, Alexander G.; Chang, Tammy
Abstract: Objective: This study aimed to assess the incremental cost‐effectiveness ratio (ICER) of a 2‐year motivational interviewing (MI) intervention versus usual primary care. Methods: A national trial was implemented in the Pediatric Research in Office Settings (PROS) network of the American Academy of Pediatrics to evaluate MI versus usual care for children (2‐8 years old; baseline BMI 85th‐97th percentiles). Health care use, food costs, provider fees, and training costs were assessed, and sensitivity analyses were conducted. Primary outcome was the ICER, calculated as cost per unit change in BMI percentile for intervention versus usual care. Results: At 2 years, 72% of enrolled parent/child dyads were retained; 312 children were included in the analysis. Mean BMI percentile point change was −4.9 and −1.8 for the intervention and control, respectively, yielding an incremental reduction of 3.1 BMI percentile points (95% CI: 1.2‐5.0). The intervention cost 1051 per dyad (658 for training DVD development). Incorporating health care and non‐health care costs, the intervention ICER was 363 (range from sensitivity analyses: cost saving, 3159) per BMI percentile point decrease per participant over 2 years. Conclusions: Training pediatricians, nurse practitioners, and registered dietitians to deliver MI‐based interventions for childhood obesity in primary care is clinically effective and acceptably cost‐effective. Future work should explore this approach in broader dissemination.